BAAMBOOZLE LEARNING MEDIA ON THE ABILITY TO WRITE ANECDOTE TEXTS IN GRADE X STUDENTS - Doce Maria Situmorang; Juni Agus Simaremare; Sarma Panggabean (Dharmas Education Journal (DE_Journal), 2024)
This study aims to determine the effect of baamboozle learning media on the writing ability of class X students of SMA Parulian 1 Medan. This study uses a quantitative experimental research method with the design of One Group Pretest Posttest Design. The population in this study was the entire class X totaling 102 students. This study used one class as a pretest and posttest class. The data analysis techniques used were normality test, homogeneity test and hypothesis test. After conducting research for the pretest and posttest classes using baamboozle learning media, the average value of the pretest class was 54.72 with a standard deviation of 12.42 and the average value of the posttest class was 83.07 with a standard deviation of 6.60. The results of the pretest and posttest class data prerequisite tests stated that the samples were normally distributed and homogeneous. From the results of the hypothesis testing, the value will be consulted with the 5% significance level table and dk (n1 + n2) - 2 = (33 + 33) - 2 = 64. By looking at the ft table value, the t table value is 5% = 1.66. Therefore, t count ˃ t table (2.852 ˃ 1.66) is obtained. This means that it can be concluded that the H0 hypothesis is rejected and the Ha hypothesis is accepted.